(3NdGUI GdJLGQH GdYGdejIs - (3efjQ GHQGgje(B, (3gfOjs ((3GdGScfOQjI(B:s (3efTCI GdeYGQa(B,s, 2004)
(3JgjFI GdefGN dJfajO HQfGeL GdNUNUI, GdJhGRf Hjf GdGSJbdGdjI hGdeSGAdI, JfejI hJWhjQ Shb QCS GdeGd, eMOOGJ fLGM YedjI GdNUNUI, GdNUNUI ef NdGd HjY MUI GdMcheI aj QCS GdeGd, SHd CNQi HOjdI ddNUNUI, Jbjje GdTQcGJ dCZQGV GdNUNUI, GWGQ dJMdjd GdJQJjHGJ GdeDSSjI deTQhYGJ GdHfjI GdJMJjI, GdJQJjHGJ GdeDSSjI GdJj JfWhj Ydi GeJdGc GdehQO ddeTQhY, GTJQGWGJ dVeGf aGYdjI GdJQJjHGJ GdeDSSjI, GdOQhS GdeSJaGOI ef NUNUI GdeDSSGJ GdYGeI(B.s
(3GdeQGLY U(B.341s
Keywords: (3GdNUNUIs; (3GdTQcGJs; (3QCS GdeGds